Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/17470210802439869
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of action on spatial working memory: The importance of selection

Abstract: We report three experiments that examine the influence of pointing-to relative to passively viewing an array of objects that participants are attempting to memorize. Recently, Chum, Bekkering, Dodd, and Pratt (2007) provided evidence that pointing to objects enhanced memory relative to passively viewing objects when pointing instruction was manipulated within trial (e.g., point to one array but passively view the other). We replicate this result but also demonstrate that when pointing instruction is blocked (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 16 publications
4
55
1
1
Order By: Relevance
“…Our data provide no evidence in support of this claim. Instead, we found that both item and order memory were significantly worse for pointed-to than for passively viewed arrays, replicating previous studies in which pointing instructions were manipulated between trials (Dodd and Shumborski 2009;Rossi-Arnaud et al 2012, 2015. Importantly, the negative effects of pointing movements were inversely related to array size, being largest for five-and six-square arrays and smallest (non significant) for eight-square arrays (see Chum et al 2007, for similar results).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our data provide no evidence in support of this claim. Instead, we found that both item and order memory were significantly worse for pointed-to than for passively viewed arrays, replicating previous studies in which pointing instructions were manipulated between trials (Dodd and Shumborski 2009;Rossi-Arnaud et al 2012, 2015. Importantly, the negative effects of pointing movements were inversely related to array size, being largest for five-and six-square arrays and smallest (non significant) for eight-square arrays (see Chum et al 2007, for similar results).…”
Section: Discussionsupporting
confidence: 88%
“…Performance in a subsequent recognition task was significantly higher for pointed-to than for passively viewed arrays, leading Chum et al (2007) to speculate that pointing movements improved attention to the spatial arrangement of the items, promoting a stronger form of egocentric (body-based) encoding. At the same time, later studies demonstrated that pointing movements significantly decreased recognition accuracy when the instructions were manipulated between trials and participants pointed to or passively encoded all the items of studied arrays (Dodd and Shumborski 2009;Rossi-Arnaud et al 2012, 2015.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, other factors, such as the mode of memory selection (Dodd & Shumborski, 2009), the precision requirements of the motor task , and whether the action decisions were freely chosen or instructed (Fleming, Mars, Gladwin, & Haggard, 2009), may also moderate interactions between motor and memory tasks. In investigating the neural correlates underlying the processes of changing one selected action plan for another, Fleming et al (2009) found differences between the neural responses related to the updating of free compared with instructed actions.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that pointing makes the feature of spatial arrangement more salient and hence improves the encoding of the arrays (cf. Dodd & Shumborski, 2009). …”
mentioning
confidence: 99%